FRI0081 WITHDRAWAL OF CONVENTIONAL SYNTHETIC DISEASE-MODIFYING ANTIRHEUMATIC DRUGS IN THE SARILUMAB OPEN-LABEL EXTEND STUDY: EFFICACY AND SAFETY ANALYSIS. (June 2019) - Curtis, Jeffrey R.; Lin, Yong; Thangavelu, Karthinathan; Stanislav, Marina; John, Gregory St.; Gómez-Centeno, Antonio; Selmi, Carlo; Huizinga, Thomas; Maldonado-Cocco, José Antonio; Bukhari, Marwan; Buttgereit, Frank
Abstract : Background: The EXTEND open-label extension study (NCT01146652 ) is collecting data on long-term treatment of RA with sarilumab as monotherapy and in combination with conventional synthetic (cs)DMARDs, predominantly methotrexate. Objectives: Post hoc analysis to compare outcomes between patients (pts) who received sarilumab monotherapy, received sarilumab +csDMARDs, or who discontinued csDMARDs during sarilumab treatment. Methods: Pts enrolled in four trials of sarilumab SC 150 or 200 mg q2w +csDMARDs (MOBILITY, NCT01061736 ; TARGET, NCT01709578 ; ASCERTAIN, NCT01768572 ; and NCT01217814 ) and an open-label sarilumab monotherapy study (ONE, NCT02121210 ) were eligible to receive open-label sarilumab SC 200 mg q2w in EXTEND, +csDMARDs if given in the parent trial. In EXTEND, csDMARDs could be stopped at investigator discretion (reasons for csDMARD withdrawal were not recorded). Post hoc analyses were conducted on three pt groups: Group 1 permanently discontinued csDMARDs at any time during Wks 0–96 of EXTEND and subsequently received sarilumab monotherapy; Group 2 continued csDMARDs; and Group 3 enrolled from the monotherapy study and never received csDMARDs. A subgroup of Group 1, comprising pts who received csDMARDs during Wks 0–12 and discontinued csDMARDs during Wks >12–96, was used for sensitivity analysis. Results: There were 42 pts in Group 1, 1851 in Group 2, and 111 in Group 3 with minor differences between groups in demographics and disease characteristics at entry into EXTEND. The proportion of pts remaining on study at 96 wks was 69%, 80% and 83% in Groups 1, 2 and 3, respectively. Similar substantial and durable response rates (CDAI ≤2.8, CDAI ≤10, DAS28-CRP <2.6, and DAS28-CRP <3.2) were observed between pts who discontinued csDMARDs, pts who continued csDMARDs, and pts who never received csDMARDs (Fig). Results for the sensitivity analysis subgroup (n=27) were consistent with Group 1. The adverse event (AE) profile was as expected for these groups. Incidence of AEs was greater in Group 1 than Groups 2 and 3 (Table), including hepatic disorders (21, 7 and 3 per 100 pt-years [PYs], respectively) and leucopenia (43, 13 and 20 per 100 PYs, respectively). Rates of infection and serious infection were lowest in pts receiving monotherapy. Conclusion: Over the 120-wk study period, pts initially on sarilumab +csDMARDs who subsequently discontinued csDMARDs maintained similar clinical responses as pts who continued sarilumab +csDMARDs or received sarilumab monotherapy throughout. The AE profile was as expected, with no new safety signals. Acknowledgement: Study funding and medical writing support (Matt Lewis, Adelphi) provided by Sanofi and Regeneron Pharmaceuticals, Inc. Disclosure of Interests: Jeffrey R. Curtis Grant/research support from: Abbvie, Amgen, BMS, Corrona, Janssen, Lilly, Myriad, Pfizer, Roche/Genentech, UCB, Consultant for: Abbvie, Amgen, BMS, Corrona, Janssen, Lilly, Myriad, Pfizer, Roche/Genentech, UCB, Yong Lin Shareholder of: Sanofi, Employee of: Sanofi, Karthinathan Thangavelu Shareholder of: Sanofi, Employee of: Sanofi, Marina Stanislav Consultant for: R-Pharm, Gregory St. John Shareholder of: Regeneron Pharmaceuticals, Inc, Employee of: Regeneron Pharmaceuticals, Inc, Antonio Gómez-Centeno Grant/research support from: Boehringer Ingelheim, Celltrion, Galapagos-Gilead, Lilly, Novartis, Pfizer, Roche, Sanofi, UCB, YL Biologics, Consultant for: Abbvie, Biogen, BMS, Celgene, Gebro, Hospira, Lilly, MSD, Pfizer, Roche, Rubio, Sandoz, Sanofi, Speakers bureau: Abbvie, BMS, Gebro, Janssen, Lilly, Menarini, MSD, Pfizer, Roche, Rubio, UCB, Sanofi, Carlo Selmi Grant/research support from: AbbVie, Janssen, MSD, Novartis, Pfizer, Consultant for: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB, Speakers bureau: AbbVie, Alfa-Sigma, Biogen, Bristol-Myrs Squibb, Celgene, Eli-Lilly, Janssen, Merck Sharp and Dohme, Novartis, Pfizer, Roche, Sanofi-Genzyme, UCB, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, José Antonio Maldonado-Cocco Consultant for: Pfizer, Merck Sharp Dohme, Sanofi – Aventis, Novartis, Bristol Myers Squibb, Roche, Boehringer Ingelheim, Schering – Plough, Abbott, UCB, Eli Lilly, Gilead, Speakers bureau: Pfizer, Merck Sharp Dohme, Sanofi – Aventis, Novartis, Bristol Myers Squibb, Roche, Boehringer Ingelheim, Schering – Plough, Abbott, UCB, Eli Lilly., Marwan Bukhari Speakers bureau: Bristol-Myers Squib, UCB celltech, Roche/Chugai, Pfizer, Abbvie, Merck, Mennarini, Sanofi-aventis, Eli-Lilly, Janssen and Novartis., Frank Buttgereit: None declared